Expanding or defending legitimacy? Why international organizations intensify self-legitimation - Henning Schmidtke; Tobias Lenz (The Review of International Organizations, 2023)
Recent decades have seen an intensification of international organizations' (IOs) attempts to justify their authority. The existing research suggests that IO representatives have scaled up self-legitimation to defend their organizations' legitimacy in light of public criticism. In contrast, this article demonstrates that IOs intensify self-legitimation to mobilize additional support from relevant audiences when their authority increases. We argue that self-legitimation aims primarily to achieve proactive legitimacy expansion instead of reactive legitimacy protection. We develop this argument in three steps. First, we draw on organizational sociology and management studies to theorize the connection between self-legitimation and an organization's life stages. Second, we introduce a novel dataset on the self-legitimation of 28 regional IOs between 1980 and 2019 and show that the intensity of self-legitimation evolves in phases. Third, we provide a multivariate statistical analysis and a brief vignette on the African Union, both of which indicate that IOs that shift from unanimity or consensus to majority voting tend to intensify self-legitimation.
Keywords: F53; F55; D72; D73; 320; Legitimation; Justification; Discourse; International organizations; Regional cooperation; Life stages